PERBEDAAN PENGARUH MODEL DISCOVERY LEARNING DAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS IPA SISWA - Ari Safitri; Yohana Setiawan (JURNAL TEMATIK, 2020)
This study aims to determine the effect differences of Discovery Learning and Problem Based Learning models on critical thinking skills of fifth grade students in natural sciences subject. This research was true experiment, pretest-posttest control group design. The sample in this research were 31 students of SD Negeri Cebongan 01 Salatiga as first experiment class and 31 students of SD Negeri Noborejo 01 Salatiga as second experiment class that were meet precondition test which the result of both samples was normal, homogeneous, and there were no significant differences. The results of this research showed that the first experimental class’ average was 74.97 and second experimental class’ average was 69.03. Based on independent sample T-test, p was 0.002 or p<0.05 it means Ho was rejected and Ha was accepted. The research concluded that there were significant differences in students critical thinking skills using the Discovery Learning model and Problem Based Learning model on the content of Natural Science learning especially for science topic: changing states of matter. In addition, from this study it could be concluded that Discovery Learning models was more suitable in learning activities in changing states of matter that Problem Based Learning.